Pathological Correlation between Number of Biopsies and Radical Surgery: Does It Make a Difference to Final Pathology? - Qayyum, Tahir (S. Karger AG, 2013)
AIMS: To evaluate whether the number of biopsies performed via transrectal ultrasound (TRUS) accurately predicts pathological parameters such as Gleason sum, prostatic intraepithelial neoplasia and perineural invasion of the final prostatectomy specimen. MATERIALS AND METHODS: The cohort consisted of 99 patients whom had undergone radical prostatectomy. Comparisons were made between the number of biopsies utilised and the presence of the pathological parameters from tissue at time of diagnosis and tissue from the final prostatectomy. RESULTS: A significant difference was noted between Gleason sum, prostatic intraepithelial neoplasia and perineural invasion from tissue at time of diagnosis irrespective of the number of biopsies utilised and tissue from the radical specimen (p < 0.001, p < 0.001, p < 0.001 respectively). No difference was noted in the mean Gleason sum when 11-14 biopsies were utilised at TRUS and the Gleason sum from the radical specimen. CONCLUSION: We have demonstrated that the number of biopsies utilised at time of TRUS for diagnosis predicts the accuracy of pathological parameters in the final radical prostatectomy specimen. We believe that 11-14 biopsies should be utilised at time of TRUS as this allows a higher accuracy in the Gleason sum and therefore allows optimum treatment plans to be devised.